PEMBINAAN KEAGAMAAN PADA PECANDU NARKOBA DI REHABILITASI INSTITUSI PENERIMA WAJIB LAPOR (IPWL) PONDOK PESANTREN SALAFIYAH HIDAYATUL MUBTADI-IEN KOTA BENGKULU - Hendro Cahyana (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2017)
The purpose of this study is an attempt to find out how the method of religious guidance on Drug Addicts at Pondok Pesantren Salafiyah Hidayatul Mubtadi-ien  Bengkulu City. The questions to be answered through this research are: (1) How is the religious activity of santri Drug Rehabilitation Rehabilitation Center at Pondok Pesantren Salafiyah Hidayatul  Mubtadi-ien  Bengkulu  City? (2) How is the  method of religious activity applied  to Drug Addicts in Pondok Pesantren Salafiyah Hidayatul  Mubtadi-ien  Bengkulu  City? (3) What are the barriers  and carrying capacity  an the process of religious guidance on Drug Addicts in Pondok Pesantren Salafiyah Hidayatul Mubtadi-ien  Bengkulu  City